Odinian Sources of Simonas Daukantas - Bončkutė, Roma (Knygotyra, 2022)
The article discusses the sources used by the national Lithuanian historian Simonas Daukantas (1793–1864) which determined the inclusion of Odin in the ranks of Lithuanian/Baltic cultural heroes in the work BUDĄ Senowęs-Lëtuwiû Kalnienû ĩr Ƶámajtiû (en. The Character of the Ancient Lithuanians–Highlanders and Lowlanders, 1845). The first source discussed is the article “De l’ère primitive des législations sacerdotales” (“On the legislative power of the priests of primeval times”) published in the magazine “Le Catholique” in 1826, on which S. Daukantas mainly relied when discussing the figure of Odin. Upon investigation, this source does not consider Odin to be the hero of the Baltic people, either. It is speculated that S. Daukantas was impressed by the laconic biography of Odin and the note added at the end that the royal families of Saxony and Denmark, the Merovingian dynasty and the Lombard princes included Odin in their genealogy. S. Daukantas analogously states that Odin is also a Lithuanian hero because, even ‘now’, there are people with the surname Odinas living in Lithuania and Samogitia. Actually, S. Daukantas’s mother was née Odinaitė. This article further discusses two other sources: Geschichte Preußens (1827, vol. 1) by Johannes Voigt (1786–1863), and Geschichte von Littauen, Kurland und Liefland (1785) by Ludwig Albrecht Gebhardi (1735–1802). It was determined that only J. Voigt briefly indicated that Odin founded Asgard near Daugava. S. Daukantas adopted this opinion in his work. On February 12, 1845, in a letter to Teodoras Narbutas (1784–1864), S. Daukantas reproached him for not including Odin in the ranks of Lithuanian cultural heroes and mentioned Le Catholique and Jntrodukcyi Maleta do historyi Dunskiej as important sources for the research pertaining to the possible Baltic origins of Odin. This inspires a hypothesis that S. Daukantas made a mistake in specifying the name of the Swiss-born historian Paul Henri Mallet because he did not write about Odin as a Lithuanian/Baltic hero in his work on Danish history. The article investigates which author’s introduction to a book on Danish history led S. Daukantas to a belief that he found information about the Lithuanian/Baltic Odin. It must have been an authoritative historian because S. Daukantas did not change his opinion about Odin when he wrote Pasakojimas apej Wejkałus Lietuwiû tautos senowie (Stories about Events in Ancient Lithuania, 1850) and emphasized that Northern writers refer to Odin as having lived and worked in Lithuania. After getting acquainted with Peter Friedrich Suhm’s introduction (Einleitung oder kritische Muthmaſsungen über die teste Abstammung und Geschichte der Nordischen Nation) to Geschichte der Dänen (1803), the study reaches the conclusion that it determined S. Daukantas’s decision about Odin’s Baltic origins. It is likely that an interdisciplinary study of the figure of Odin would finally allow us to confirm or reject this belief of S. Daukantas.